Computational fluid dynamics for sub-atmospheric pressure analysis in pipe drainage (2019)
The occurrence of sub-atmospheric pressure in the drainage of pipelines containing an air pocket has been known as a major cause of several serious problems. Accordingly, some system malfunction and pipe buckling events have been reported in the literature. This case has been studied experimentally and numerically in the current research considering objectives for a better understanding of: (i) the emptying process, (ii) the main parameters influencing the drainage, and (iii) the air-water interface deformation. Also, this research demonstrates the ability of a computational fluid dynamic (CFD) model in the simulation of this event. The effects of the air pocket size, the percentage and the time of valve opening on the pressure variation have been studied. Results show the pipeline drainage mostly occurs due to backflow air intrusion. The worst case scenario is associated with a fast valve opening when a tiny air pocket exists in the pipeline. © 2019, © 2019 International Association for Hydro-Environment Engineering and Research.